PERAN MEDIASI KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA PELANGGAN MARKETPLACE TOKOPEDIA - Nirsetyo Wahdi; Aprih Santoso (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
The object of this research is a well-known marketplace, namely Tokopedia, with limited respondents in the city of Semarang. This research aims to determine the role of customer satisfaction as a mediating variable in influencing customer loyalty. The research sample was obtained as many as 100 respondents using a sampling technique, namely purposive sampling, namely the technique of determining the sample with certain considerations or criteria. The data analysis technique used multiple linear regression with mediating or intervening effects. The results showed that there was a significant effect of product quality, service quality and trust partially on customer satisfaction, there was a significant effect of product quality, service quality, trust and customer satisfaction partially on customer loyalty. The results of the first mediating effect found that customer satisfaction was able to mediate the effect of product quality on customer loyalty. the direct influence value is 0.16 < the indirect effect is 0.18. The results of the second mediating effect found that customer satisfaction was able to mediate the effect of service quality on customer loyalty. the direct influence value is 0.16 < the indirect effect is 0.17. The results of the second mediation effect obtained that customer satisfaction was not able to mediate the effect of trust on customer loyalty. the direct influence value is 0.22 > the indirect effect is 0.09.